(untitled) (Cadernos de Sociomuseologia, 2012)
This paper is based on a study of visitors to the museums in the Alt Pirineu and Aran region (Catalonia, Spain). We describe the characteristics of the museums’ users and analyse the relationship between the museums and the local community. We highlight the importance of these facilities for local development, and the need to consider and prioritize their role as culture centres for the region’s population. Keywords: Visitor studies, local community, local museum, High Pyrenees, Aran Valley.